Genome-Wide Identification and Functional Characterization of the BAHD Acyltransferase Gene Family in Brassica napus L. - Yuanyuan Liu; Xingzhi Wei; Yiwei Liu; Yunshan Tang; Shulin Shen; Jie Xu; Lulu Chen; Cunmin Qu; Huiyan Zhao; Hai Du; Huafang Wan; Nengwen Yin; et al. (Plants)
The BAHD acyltransferase family plays a critical role in plant secondary metabolism by catalyzing acyl transfer reactions that are essential for synthesizing metabolites involved in environmental adaptation. However, systematic investigation of this superfamily in Brassica napus has not been reported. In this study, 158 BnaBAHD genes were identified by comprehensive analyses of evolutionary relationships, motif structures, chromosomal distribution, gene collinearity, and selection pressures, and these genes were phylogenetically classified into five clades harboring conserved catalytic domains (HXXXD and DFGWG). Transient overexpression combined with metabolomic profiling demonstrated that two homologous seed-specific Clade V members, BnaBAHD040 and BnaBAHD120, which exhibited elevated expression during late seed development, significantly enhanced the accumulation of acylated metabolites contributing to biotic/abiotic stress resistance. This study provides the first experimental validation of the catalytic functions of BAHD enzymes in B. napus, establishing a theoretical foundation for leveraging this gene family in genetic improvement to develop novel rapeseed cultivars with enhanced stress tolerance and yield.